Optimal timing of follow-up cardiac magnetic resonance in patients with acute myocarditis. (14th October 2021) - Ciabatti, M; Ferri, L; Camporeale, A; Saletti, E; Chioccioli, M; Felici, M; Martinese, L; Milani, V; Sabini, A; Pieroni, M; Lombardi, M; Bolognese, L
Abstract: Background: Cardiac magnetic resonance (CMR) plays a central role in the diagnosis, follow-up and prognostic stratification of acute myocarditis. Several CMR features, including the extent of late gadolinium enhancement (LGE) at baseline, have been proposed as factors associated with a worse outcome. Recent studies evaluated temporal evolution of LGE and edema repeating CMR either at 6 months or at 12 months, demonstrating that persistence or worsening of LGE represents a negative prognostic marker. However, the time-course of edema resolution and LGE stabilization is currently unknown and therefore the optimal timing to repeat CMR for acute myocarditis prognostic stratification remains unclear. Purpose: We aimed to assess the time course of edema and LGE evolution in order to identify the optimal timing to repeat CMR in patients with acute myocarditis. Methods: We enrolled 36 patients with a diagnosis of acute myocarditis according to ESC position statement definition. All patients underwent CMR at clinical presentation (CMR-1), after 3–4 months (CMR-2) and after 12-months (CMR-3) follow-up. CMR evaluation included assessment of edema and LGE, and evaluation of structural and functional parameters including left (LVEF) and right ventricular ejection fraction (RVEF), left (LVGLS) and right ventricular global longitudinal strain (RVGLS) and indexed left ventricular mass (iLVM). After CMR-3 all patients were followed-up by yearly clinical evaluation, electrocardiogram (ECG) and 2D-echocardiography. Results: The mean age was 28, 8±10, 3 years with 35 (97%) being male. All patients showed edema and LGE at CMR-1 with a LVEF of 58, 5±12, 2. At CMR-2 a significant reduction of edema (T2 positive segments 0, 4±0, 9 vs. 4, 1±3, 2 p<0.0001) and LGE extent (LGE ≥5SD 5, 1±5, 3 vs. 9, 6±8, 4 p<0.0001) was observed, with only 3 patients showing edema persistence. A significant improvement of LVEF (62, 7±5, 6 vs. 58, 5±12, 2 p<0.05), RVGLS (−24, 4±5, 4 vs. −21, 6±7, 4 p<0.05), associated with a significant reduction of iLVM (71, 2±13, 7 vs 78, 1±15, 2 g/mq) was also observed. At CMR-3 no further significant reduction of LGE extent was observed with no further improvement of LVEF, RVGLS and iLVM. In the 3 patients with persisting edema at CMR-2, a complete resolution was observed at CMR-3. After a mean follow-up of 60±23 months, no major cardiovascular events nor myocarditis recurrences were observed, with no patients showing left ventricular dysfunction nor progression to dilated cardiomyopathy at 2D-echocardiography. Conclusions: In most patients with acute myocarditis a complete resolution of the inflammatory process with LGE stabilization and normalization of left ventricular function and mass can be observed after 3–4 months. Further CMR assessment should limited to patients with persisting oedema at 3–4 months CMR. Our findings suggest to redefine the follow-up schedule and imaging-based prognostic stratification strategies in patients with acute myocarditis. Funding Acknowledgement: Type of funding sources: None.